THE ROLE OF POST-DIVORCE CHILDREN'S RIGHTS ADVOCACY IN INDONESIA - Ferlan Niko; Nanang Wartono; Hidayatullah Ismail; Sutomo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Children's rights advocacy is a series of systematic efforts made by individuals, groups, institutions, or organizations to protect, promote, and ensure the fulfillment of children's rights in accordance with international and national legal standards and norms. This advocacy aims to fight for the best interests of children so that their rights such as the right to protection, education, health, and participation are respected and guaranteed by the state, family, and society, especially in Indonesia which is greatly influenced by religious norms, morals and decency in addition to legal norms. However, children's rights can be threatened due to divorce events that occur between their parents. The divorce triggers those related to the interests of the child whether they are fulfilled or not fulfilled. The divorce process not only has an impact on married couples, but also has significant implications for the children who are part of the family. Children who are in divorce situations are prone to experiencing various negative impacts, both psychological, social, and economic. This study examines the role of advocacy for children's rights after divorce and what are the factors that make the role of advocacy effective. The research uses normative research methods. Normative legal research itself is legal research that is carried out by researching literature materials or secondary data. To then conduct an analysis and study of the ministry a conclusion is taken.